Relatório do estágio curricular supervisionado em medicina veterinária área de concentração: bovinocultura de leite - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This report aims to present and describe the locations chosen for the Supervised Curricular Internship in Veterinary Medicine (ECSMV), and the activities developed, in addition to discussing two conditions abomasal ulcer and uterine torsion, in the form of case reports. The ECSMV's area of concentration was dairy farming, under the guidance of Professor Tiago Gallina Corrêa and supervision of Veterinary Doctor Laura da Nova Cruz Pegorini and Veterinary Doctor Fábio de Souza Guagnini. The internship was divided into two stages, the first being carried out with DVM Laura and the second with DVM Fábio. The internship period was from August 7, 2023 to November 3, 2023, totaling 520 hours. During it, it was possible to follow activities in the area of reproductive management, veterinary medical clinic, surgical clinic and preventive medicine. Carrying out the ECSMV was of great importance in reconciling the theoretical knowledge obtained during graduation with practical experience. Carrying out the internship with two professionals provided monitoring of different behaviors and the exchange of experiences, contributing to the development of critical thinking and adding knowledge in the area.
Curricular internship report supervised in veterinary medicine Area of concentration: dairy cattle farming
Keywords: Dairy cattle; Abomasal ulcer; Úlcera de abomaso; Torção uterina; Uterine torsion; Bovinos de leite; CNPQ::CIENCIAS AGRARIAS